2020
DOI: 10.1177/1073191120936357
|View full text |Cite
|
Sign up to set email alerts
|

Personality Disorders in the ICD-11: Spanish Validation of the PiCD and the SASPD in a Mixed Community and Clinical Sample

Abstract: The International Classification of Diseases–11th revision (ICD-11) classification of personality disorders is the official diagnostic system that is used all over the world, and it has recently been renewed. However, as yet very few data are available on its performance. This study examines the Personality Inventory for ICD-11 (PiCD), which assesses the personality domains of the system, and the Standardized Assessment of Severity of Personality Disorder (SASPD), which determines severity. The Spanish version… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
1
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 59 publications
2
40
1
5
Order By: Relevance
“…They also reported a five-factor solution which they suggested supported separate, independent anankastia and disinhibition factors. However, each of the two factors were actually defined by both anankastia and disinhibition items, as has been found previously (Carnovale et al, 2020;Gutierrez et al, in press; J. R. Oltmanns & Widiger, 2018). The findings though were limited with respect to a validation of the IPiC-confined simply to its factor structure.…”
mentioning
confidence: 72%
“…They also reported a five-factor solution which they suggested supported separate, independent anankastia and disinhibition factors. However, each of the two factors were actually defined by both anankastia and disinhibition items, as has been found previously (Carnovale et al, 2020;Gutierrez et al, in press; J. R. Oltmanns & Widiger, 2018). The findings though were limited with respect to a validation of the IPiC-confined simply to its factor structure.…”
mentioning
confidence: 72%
“…Overall, nine studies were conducted on a clinical psychiatry sample, eight were conducted in the general population, and two studies were undertaken in both of these groups. Sample size ranged from 124 in a study of patients with PD (35) to 2,522 in a study of participants in a community sample (44). Most of the studies (n = 18) addressed the question of diagnostic validity, while a single study examined the clinical utility of the ICD-11 PD model.…”
Section: Resultsmentioning
confidence: 99%
“…Studies on the ICD-11 PD model and its factorial structure suggested using either a five-factor solution or four-factor solutions, resulting in a single low disinhibition/high anankastia domain (38,(40)(41)(42)(43)(44)(45)(46)(47)(48)(49). In this multidimensional structure, OCPD could be distinguished by a high score on anankastia traits, automatically resulting in low disinhibition traits.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A four-factor solution consisting of negative affectivity, detachment, and dissociality factors, and a bipolar anankastia-versus-disinhibition factor fit the data better than a five-factor solution with separate factors for anankastia and disinhibition. In a five-factor itemlevel solution, the bipolar anankastia-versus-disinhibition factor divided into two bipolar anankastia-versus-disinhibition factors, a finding that has since been replicated several times (6)(7)(8). Notably the four-factor structure with a bipolar factor is somewhat confusing, but the factor structure has no bearing on clinical assessment, because a clinician would score and interpret the PiCD for five separate domains regardless of the factor structure.…”
Section: Recent Findings Personality Inventory For Icd-11 (Picd)mentioning
confidence: 99%